Containing the Multitudes: Critical Reflections on the Concept of the “International Student” Through a Pluriversal Lens - Rose-Redwood, CindyAnn; Rose-Redwood, Reuben (Journal of International Students, 2023)
A growing body of scholarship has examined different aspects of the international student experience in higher education institutions, yet few studies have critically interrogated the very concept of the “international student” itself. In this article, we consider the different ways in which politico-legal practices of boundary-making have produced categorization schemes that demarcate the boundary between the national “Self” and the international “Other.” These legal categories of the “domestic” and “international” student serve as the discursive grid through which student populations are rendered legible by university administrators, student affairs practitioners, and scholars. We argue that the socio-cultural worlds of international students are not reducible to the homogenizing logics of politico-legal and institutional categorization, and that they should be reimagined through a pluriversal lens – where multiple worlds of difference can co-exist in spite of persistent efforts to contain the multitudes within the rigid, fixed, and mutually exclusive categories of the nation-state.